Integrasi Tadabur Al-Quran dalam Bibliotherapy untuk Pengembangan Diri Profesional - Fitria Husna (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
Self-development is a crucial competence for navigating the professional world; however, many individuals face significant barriers in optimizing this potential. This study aims to formulate an integrative model of Quranic Tadabur and bibliotherapy as a professional therapeutic intervention in counseling, addressing gaps in existing literature. Using a library research method with content analysis, the findings indicate that Quranic Tadabur effectively enhances essential self-development skills, including self-awareness, work motivation, problem-solving, time management, emotional regulation, critical and creative thinking, and social collaboration. Within the bibliotherapy framework, the self-development process is structured through stages of motivation, incubation, follow-up, and evaluation. Furthermore, several counseling techniques are proposed, such as self-management, minimal contact, counselor-led management, and directed counseling, to support individual growth. This integrative approach highlights the role of spirituality in fostering holistic personal and professional development. The study contributes theoretically to the advancement of spirituality-based counseling models, particularly in the context of modern career development, and offers a conceptual foundation for future empirical research.